2020
DOI: 10.3390/cells9081848
|View full text |Cite
|
Sign up to set email alerts
|

Schwann Cell Cultures: Biology, Technology and Therapeutics

Abstract: Schwann cell (SC) cultures from experimental animals and human donors can be prepared using nearly any type of nerve at any stage of maturation to render stage- and patient-specific populations. Methods to isolate, purify, expand in number, and differentiate SCs from adult, postnatal and embryonic sources are efficient and reproducible as these have resulted from accumulated refinements introduced over many decades of work. Albeit some exceptions, SCs can be passaged extensively while maintaining their normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 142 publications
(235 reference statements)
0
35
0
Order By: Relevance
“…Stem cell-based therapies for peripheral nerve regeneration have been widely explored within preclinical and clinical studies ( Sullivan et al, 2016 ; Jiang et al, 2017 ; Kubiak et al, 2020 ). Although Schwann cells are key cells involved in the process of nerve regeneration, their clinical application entails limitations ( Monje, 2020 ). Along with other researchers, we have shown that SCLCs induced from mesenchymal stem cells have even better outcomes relating to peripheral nerve generation than do Schwann cells ( Jiang et al, 2017 ; Chen et al, 2019 ; Hopf et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stem cell-based therapies for peripheral nerve regeneration have been widely explored within preclinical and clinical studies ( Sullivan et al, 2016 ; Jiang et al, 2017 ; Kubiak et al, 2020 ). Although Schwann cells are key cells involved in the process of nerve regeneration, their clinical application entails limitations ( Monje, 2020 ). Along with other researchers, we have shown that SCLCs induced from mesenchymal stem cells have even better outcomes relating to peripheral nerve generation than do Schwann cells ( Jiang et al, 2017 ; Chen et al, 2019 ; Hopf et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…As the primary glia and myelin-forming cells within the peripheral nervous system, Schwann cells play an important role in nerve regeneration ( Jessen et al, 2015 ; Bolívar et al, 2020 ; Nocera and Jacob, 2020 ), initiating a reprogramming process after PNI in which they demyelinate and transdifferentiate into repair Schwann cells ( Nocera and Jacob, 2020 ). Several transcription factors and pathways support Schwann cell proliferation, migration, and survival during this process ( Monje, 2020 ; Nocera and Jacob, 2020 ). Notable among these factors are JUN, SOX2, and STAT3, which play a critical role in Schwann cell reprogramming ( Nocera and Jacob, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…SC monocultures are established from enzymatic digestion of neonatal mouse sciatic nerves in a plethora of recent studies because the preparation technique is less cumbersome. Neonatal nerves contain underdeveloped connective tissues and unmyelinated fibers and can be easily digested to render copious amounts of primary SC (Monje, 2020 ). Myelination can be induced in these cells by the addition of cAMP in substantially large concentrations (Arthur-Farraj et al, 2011 ; Bacallao and Monje, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…As for SC monocultures, the phenotype of SC in culture; irrespective of the source, is highly peculiar as these cells express several makers of the Schwann cell lineage including those of SCP, iSC and the repair phenotype that arises post nerve injury (Monje, 2020 ). In our study, we wanted to determine the myelination potency of coculture-derived SC monocultures and compare that to SC monocultures established from neonatal nerves which largely comprise of iSC and pro-mSC (Monje, 2020 ; Figure 4 ). Our observations demonstrate firstly that SC monocultures derived from DIV7 cocultures are similar to cultures established from neonatal peripheral nerves in their potential to differentiate into mSC.…”
Section: Discussionmentioning
confidence: 99%
“…Primary embryonic rat tissue has long served as the basis for peripheral nerve studies and has elucidated mechanisms of myelination by Schwann cells dating back to the 1980s (Eldridge et al 1987). However, myelination of human axons by human Schwann cells in vitro has been much more elusive (Monje 2020). These myelination studies have long existed within 2D systems such as those described above wherein cells are cultured atop ECM coated glass coverslips without any discrete compartmentalization.…”
Section: Induction Of Myelinationmentioning
confidence: 99%